Preventing Mass Atrocities: Ideological Strategies and Interventions - Leader Maynard, Jonathan (2015)
Both scholars and international actors frequently stress the important role played by anti-civilian ideologies in escalating risks of mass atrocities against civilians. Yet strategies to combat and counter anti-civilian ideologies remain an uncertain and understudied component of atrocity prevention, and scepticism about their efficacy is to be expected. This paper provides a preliminary framework for thinking about strategies and interventions designed to counter the ideological causes of mass atrocities. First, I briefly clarify what existing research seems to suggest the role of ideology in mass atrocities is, and is not. I caution against cruder or overly strong theses about the role ideology plays, but clarify that whilst ideology’s actual causal impact is varying and complex, it is also significant. Second, I clarify what ideological interventions and strategies might be reasonably expected to do, and comparatively assess them against more dominant existing prevention tools to show that their preventive potential is sufficiently high to warrant usage. Finally, I provide guidelines on how the effort to formulate ideological strategies and interventions for preventing mass atrocities should best proceed.